Odd jobs, and beggars: permanent sample of inequality and poverty in the city of Cúcuta, North Santander, Colombia - Castro, William Rodrigo Avendaño; Montes, Luisa Stella Paz (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper makes a theoretical and reflexive approach to inequality and poverty in San José de Cúcuta, North Santander, border between Colombia and Venezuela. It presents factors associated with unemployment, which contribute to begging, alms and odd jobs from a socio–economic environment, collects basic information applying a semi-structured survey (random) to a specific population: determining agents of a permanent practice of informal economy in the city. The results refer to a population sample from, for the most part, to a different regions of the country, associated with such aspects of not only economic, but social and forced displacement because of internal armed conflict and violence (IDPs: Internally Displaced Persons), leading to their establishment in the city which has generated health, education, security problems, among others.